S100A10 knockdown exacerbates phenylephrine-induced cardiomyocyte hypertrophy via modulating mitochondrial oxidative phosphorylation - Xu, Feixue; Chen, Yajie; Xu, Man; Li, Dan; Lu, Yinshan; Zhang, Meng; Li, Jiahao; Li, Wanyi; Guo, Yingying (Frontiers in Genetics, 2025)
BackgroundMitochondrial dysfunction is a well-established hallmark of pathological cardiac hypertrophy, though its underlying mechanisms are not fully understood. S100A10, a calcium-binding protein, participates in diverse cellular processes, including the regulation of mTOR signaling and mitochondrial function. This study aims to investigate the role and mechanistic basis of S100A10 in phenylephrine (PE)-induced cardiomyocyte hypertrophy.MethodsPrimary neonatal rat cardiomyocytes (NRVMs) were treated with phenylephrine (PE) to induce hypertrophy. S100A10 expression was modulated by siRNA knockdown. The interaction between S100A10 and ANXA2 was confirmed by co-immunoprecipitation. mTOR pathway activation was analyzed by Western blotting. Mitochondrial function was assessed by measuring the expression of electron transport chain complexes, mitochondrial membrane potential using JC-1 staining, and mitochondrial oxidative stress using MitoSOX.ResultsS100A10 expression was significantly upregulated in hypertrophic murine hearts. We further demonstrated that S100A10 interacts with ANXA2 to activate the mTOR/4E-BP signaling pathway. Knockdown of S100A10 in NRVMs suppressed the expression of mitochondrial respiratory chain proteins, impaired oxidative phosphorylation activity, and reduced mitochondrial membrane potential and ATP production.ConclusionThese findings indicate that downregulation of S100A10 exacerbates PE-induced cardiomyocyte hypertrophy and uncover a novel function of S100A10 in modulating mitochondrial respiratory chain protein levels, potentially through the mTOR/4E-BP pathway. This may provide a theoretical basis for future therapeutic strategies.